Processos de subjetivação postos em funcionamento pelo discurso da educação (matemática) escolar quilombola - Suzarte, Ayrton Pereira (2025)
This dissertation focuses on the process of constituting the quilombola subject in the context of quilombola school education, with an emphasis on mathematics, based on Foucauldian theories. The main objective is to understand the processes of subjectivation put into operation by the discourse of quilombola school (mathematics) education. Adopting a qualitative approach based on post-structuralist assumptions, the research was conducted through a documentary analysis, using as sources the official curricular documents related to quilombola school education and the mathematics textbooks approved in the Programa Nacional do Livro Didático (PNLD) 2024–2027. For this purpose, the study examined the Resolutions which establishes the Curricular Guidelines for Quilombola School Education. The analysis of these curricular guidelines enabled the identification of nine quilombola subject positions articulated by the discourse of quilombola school education. These positions demand a quilombola subject who affirms their identity, values their memories, recognizes their territories, and engages in the struggle for rights and resistance against historical erasure. These positions construct an image of a quilombola subject as a protagonist, aware of their history and their political and social role. The analysis of the textbook aimed to understand how this educational material operates with hegemonic norms when considering the formation of quilombola subjects — that is, critical individuals conscious of their cultural and historical belonging, in alignment with the principles of the Curricular Guidelines. Finally, this study points out that contributing to a critical understanding of power dynamics in quilombola school education, questioning hegemonic discourses, and fostering more authentic forms of expression and resistance in the educational context requires recognizing the diversity and complexity of quilombola experiences, attentively listening to these communities, and valuing their knowledge, memories, and cultural practices. Moreover, it demands the construction of pedagogical practices that promote the autonomy, representativeness, and insurgency of these subjects in the educational space.